Concentration of Ammonia Pollution in Madura Traditional Salt Production Water - Eka Nurrahema Ning Asih; Ary Giri Dwi Kartika; Makhfud Efendy; Kartika Dewi; Bahri Fadloli; Arya Galin Fakhrul Islami Zain (Journal Omni-Akuatika, 2022)
Ammonia (NH3) is one of the impurities in salt-producing water, which is often found in the traditional salt ponds of the Madurese. The purpose of this study was to determine the concentration of ammonia contamination as an impurity in salt production process water from raw water, reservoir ponds, evaporator ponds to geomembrane crystallizer ponds when salt production takes place in the salt ponds of Tanjungan Village, Bangkalan Regency. Determination of ammonia concentration using the phenate method based on SNI 06-6989.30-2005 with a spectrophotometer reading tool (UV-2700 Serial No. A11674900027) at a wavelength of 420 nm. The average concentration of ammonia as an impurity in raw materials in traditional pond ponds in Tajungan village, namely raw water is 2.31±0.24 mg/L, reservoir ponds are 2.56±0.57 mg/L, evaporator ponds are 2, 39±0.84 mg/L and the geomembrane crystallizer ponds are 1.37±0.09 mg/L. The highest average ammonia concentration was found in the reservoir ponds raw saltwater sample, while the lowest concentration was found in the geomembrane crystallizer ponds sample. The high average ammonia concentration in the salt ponds of Tajungan Village, Bangkalan Regency indicates that all raw saltwater in these ponds is contaminated with ammonia. The high concentration of ammonia in the salt ponds may be due to the entry of household waste. Keywords: (NH3), raw water, reservoir ponds, evaporation ponds, geomembrane crystallizer ponds